CT ANGIOGRAPHY FOR DETECTING THE CAUSE OF INTRACRANIAL HEMORRHAGE IN THE EMERGENCY DEPARTMENT - E. I. Zyablova; V. V. Tkachev; V. A. Porhanov (Инновационная медицина Кубани, 2021)
Background Intracranial hemorrhage is the most serious manifestation of a ruptured cerebral aneurysm, and subarachnoid hemorrhage (SAH) is the most common clinical and anatomical form. The treatment strategy for SAH varies from conservative to emergency surgical treatment and depends on the source of the hemorrhage. Currently, the search for sources is carried out using various methods of diagnostic radiology.Objective To compare the images of intracranial arteries obtained by computed tomography (CT)  angiography with the data of cerebral angiography in the acute period of hemorrhage in the subarachnoid space.Material and Methods We retrospectively analyzed the medical records of 242 patients with acute SAHs from September 2017 to September 2019, examined in the emergency room of the Research Institute – Ochapovsky Regional Hospital no. 1.Results According to CT angiography, the initially occult vascular lesion was verified in 212 patients (87%), of which in 84.0% of cases (205 patients) the cause of SAH was ruptured cerebral aneurysms. In 3 patients, ruptures of arteriovenous malformations were detected (1.2%). In 4 patients, the “cerebral aneurysms” diagnosis was excluded due to the establishment of a hypertensive nature of intracranial hemorrhage (1.7%). In 30 patients, CT angiography revealed no vascular pathology. According to the results of CT angiography only, 225 patients (93%) were microsurgically operated on, and 12 patients (5%) were operated on using intravascular access. Among 30 patients whose vascular pathology was not detected by CT angiography, 6 patients were found to have single aneurysms according to cerebral angiography: the internal carotid artery – in 3 patients, the middle cerebral artery – in 2, and the pericallous artery – in 1 patient.Conclusion CT angiography is a key tool of non-invasive diagnosis of the source of SAH in emergency  departments. The absence of vascular pathology on CT angiography in the presence of massive basal SAH, the detection of multiple and “complex” aneurysms, as well as cerebral arteriovenous malformations of the brain during CT angiography remain indications for cerebral angiography.